Ethics and AI Technology: Does Artificial Intelligence Make Us Better? - putri, fara rahma (Maliki Interdisciplinary Journal, 2025)
As technology continues to develop in this era, humans must constantly adapt to changes so that technology can be used properly and wisely. Ethics are very important and closely related to the use of artificial intelligence, or what we commonly refer to as AI. Ethics are the benchmark for humans in using AI to carry out their individual and social lives. The use of AI as a tool in everyday life requires humans to understand the positive and negative impacts of AI on their lives. If AI is used properly, it will make activities such as working, learning, and carrying out daily human activities more effective and efficient. However, if humans cannot adapt and use AI properly, it will cause negative effects such as job losses, increased laziness in learning and thinking, data privacy and security issues, and social conflicts due to hate speech on social media. It can be concluded that ethics plays a very important role in the use of AI to help humans carry out their daily activities.